1991
DOI: 10.1152/ajpheart.1991.260.2.h542
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and fasting determine postischemic glucose utilization in isolated working rat hearts

Abstract: To assess the effects of endogenous substrate on glucose utilization after 15 min of ischemia, we perfused isolated working rat hearts from fed and fasted (16 h) animals with glucose and the positron-emitting glucose analogue 2-[18F]fluoro-2-deoxy-D-glucose (2-FDG). Hearts were perfused in a recirculating system with bicarbonate buffer containing glucose (10 mM) and 2-FDG (0.5 microCi/ml). Mechanical performance and 2-FDG uptake were measured on-line, and glucose and lactate metabolic rates were calculated. Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 0 publications
4
20
0
Order By: Relevance
“…26 Unlike liver and skeletal muscle, heart muscle increases its glycogen content with fasting. 27 This observation is consistent with the general principle that fatty acids, the predominant fuel for the heart during fasting, inhibit glycolysis more than glucose uptake, thereby rerouting glucose toward glycogen synthesis. Glycogen stores are also increased by insulin, from the simultaneous stimulation of glucose transport and glycogen synthase activity.…”
Section: Glycogen Metabolismsupporting
confidence: 85%
“…26 Unlike liver and skeletal muscle, heart muscle increases its glycogen content with fasting. 27 This observation is consistent with the general principle that fatty acids, the predominant fuel for the heart during fasting, inhibit glycolysis more than glucose uptake, thereby rerouting glucose toward glycogen synthesis. Glycogen stores are also increased by insulin, from the simultaneous stimulation of glucose transport and glycogen synthase activity.…”
Section: Glycogen Metabolismsupporting
confidence: 85%
“…Nine adult mongrel dogs weighing [24][25][26][27][28][29][30][31][32][33][34][35] kg (mean, 28.2+3.2 kg) were studied. Animals were anesthetized with sodium thiamylal (Surital) 2 mg/kg i.v.…”
Section: Animal Instrumentationmentioning
confidence: 99%
“…The development of a simplified graphical method to determine rates of glucose uptake based on the trapping oftracer in an irreversible compartment (4,5), has allowed studies ofthe kinetics ofglucose uptake by external detection in the intact heart both in vitro and in vivo. Initial work on the rapid kinetic analysis of glucose metabolism in the intact heart has been reported (6)(7)(8) and has suggested that the relationship between uptake of the tracer, 2-[ '8F Ifluoro-2-deoxy-D-glucose, and uptake ofthe tracee, glucose, is not always constant.…”
Section: Introductionmentioning
confidence: 99%